S55 Mir-181: a potential biomarker of acute muscle wasting?. (14th November 2013) - Bloch, SAA; Kemp, PR; Griffiths, MJD; Polkey, MI
Abstract : Introduction and Objectives: Acute muscle wasting in the critically ill is common and associated with significant morbidity and mortality. Although some aetiological risk factors are recognised it is difficult to predict those who will develop muscle wasting. The ability to predict who will go on to develop muscle wasting or to detect muscle wasting prior to it becoming clinically significant would provide the opportunity to intervene at an early stage with strength training or anabolic agents. MicroRNAs are small non coding RNA that are thought to modulate post transcriptional regulation of translation. Since we have previously found that microRNA expression in skeletal muscle relates to muscle weakness in COPD ( Thorax 2012;67:26–34) and in blood are associated with skeletal muscle phenotype ( Thorax in press PMID 23814167) we hypothesised that plasma microRNAs could be biomarkers of ICU acquired muscle weakness. Methods: In a prospective observational study ( Crit Care Med 2013;41:982–989) of 42 patients undergoing elective high-risk cardiothoracic surgery plasma levels of selected microRNAs were assayed pre-operatively and over the first week post operatively. Those who developed muscle wasting were identified by ultrasound. Main Results: 55% (23 of the 42) of patients developed muscle atrophy. Rise in mir-181 was significantly higher at day 2 post surgery in those who developed muscle wasting compared to those who did not (p = 0.03, Figure 1 ). A rise in mir-181 of greater than 1.7 times baseline at day 2 post surgery has a 90% specificity for muscle wasting, (with 55% sensitivity). Other microRNAs did not show significant differences between the groups. Conclusion: Mir-181 has been shown to be involved in both regulation of inflammation and muscle regeneration and differentiation. Mir-181 provides a potential biomarker of developing muscle wasting and with further development in the future may prove to be useful in directing treatment. Funding: This work is funded by an MRC Clinical fellowship to Dr Bloch and supported by the NIHR Respiratory BRU at the Royal Brompton and Harefiled NHS Trust and Imperial College who part fund the salries of MIP and MG